Pengaruh Penambahan Tepung Rumput Laut (Eucheuma cottonii) dan Rasio Pasta Ubi Jalar Ungu (Ipommoea batatas var Ayamurasaki) – Tepung Terigu pada Karakteristik Mie Basah - Sari, Putri Meutia; Muhardina, Virna; Hakim, Lukmanul; Rahmiati, Tengku Mia; Sunartaty, Rita; Irmayadani, Irmayadani; safitri, isna; Aprita, ika Rezvani; Luciana, Lisma (Jurnal Teknologi Pengolahan Pertanian, 2023)
Seaweed (Eucheuma cottonii) is an abundant marine commodity in Indonesia, used for gelatin and carrageenan in food, pharmaceutical, and cosmetics industries, while sweet potato is one of crop commodities as a source of carbohydrates having potential for food diversification and agro-industry, such as noodle. The main concern characteristic of noodle is chewiness and elasticity. The aim of this study was to determine the effect of seaweed flour addition and the ratio of purple of sweet potato paste on quality of noodle. The research was conducted by using Completely Randomized Design (CRD) consisting of two factors, namely seaweed flour concentration (P) (10%, 20%, 30%), and ratio of sweet potato paste (R) (50:50, 60:40, 70:30). The results showed that the addition of seaweed flour (P) had no significant effect on water content, cooking time, organoleptic test regarding color, taste, and elasticity, but it had effect on ash content, water absorption capacity, and breaking strength. On the other hand, ratio of sweet potato had no significant effect on ash content, breaking strength, cooking time, and organoleptic tests of color, taste, and elasticity. The interaction between those two factors had effects on water and ash content. The best treatment was adding 30% of seaweed flour with ratio of sweet potato paste 60:40, in which 62.2% water content, 0.92% ash, 61% water absorption, 13 cm breaking strength, 2.15 minutes, and usual acceptance of organoleptic parameters (color, taste, elasticity). Keywords: Elasticity; noodle; purple sweet potato paste; seaweed flour